Climate change impacts on crop yields [In Ethiopia's agrifood system: Past trends, present challenges, and future scenarios] - Thomas, Timothy S.; Dorosh, Paul A.; Robertson, Richard D. (International Food Policy Research Institute, 2020)
Chapter 4, “Climate Change Impacts on Crop Yields,” presents results of model simulations of crop yields in Ethiopia through 2085. The analysis draws on climate outcomes from 32 global climate models and an agronomic crop model to estimate effects of expected higher temperatures and, for most of Ethiopia, increased rainfall. The simulation results suggest that climate change will likely have only relatively small effects on average yields of maize, wheat, and sorghum in Ethiopia up to 2055, as agronomic conditions for cultivation of these crops may actually improve in large parts of the country. Nonetheless, crop yields will need to increase over time to enable cereal production to keep pace with expected demand growth due to increases in population and per capita incomes. Moreover, even if future changes in climate have only moderate impacts on average crop yields in Ethiopia, weather outcomes and consequent crop yields are likely to become more variable in the future.